Stomata Index of Cattleya sp. Lindl., Planlet in Drought-Stress Conditions - Tara Sesafia Paletri; Endang Nurcahyani; Yulianty Yulianty; Rochmah Agustrina (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Cattleya was one of the most popular orchids by Indonesian. Constraints in cultivating Cattleya included the lack of water availability in an area, causing drought stress. Stress in drought in vitro can be simulated by adding Poly Ethylene Glycol 6000 and growth regulators in atonic form. The purpose was to determine the effect of atonic solution and PEG 6000 on the stomata index toward in vitro drought stress conditions. This study was carried out in a 3 x 3 factorial experiment. Factor A was an atonic solution with 3 concentration levels: 0 mL/L, 2 mL/L, and 3 mL/L. Factor B is PEG 6000 with 3 concentration levels: 0% b/v, 20% b/v, 25% b/v. The results showed that the higher the concentration of PEG 6000 and atonic concentrations caused a decrease in the stomata index of Cattleya orchid plantlets under drought stress conditions in vitro.